Estudio de relaciones de catalizador en la acetilación de almidón de papa china para la aplicación en Film - Jara Romero, Denisse Alejandra; Belduma Belduma, Diego Bratzon (My University, 2024)
The purpose of this work was to develop and evaluate the physical and mechanical properties of films made from acetylated starch of Chinese potato Colocasia esculenta with microcrystalline cellulose and oregano essential oil (Origanum vulgare). For the extraction of native starch, wet grinding was applied with a 0.1% citric acid solution (w / v) where a yield of 19.55 ± 0.66% was obtained, then a chemical modification was carried out by acetylation using three different stoichiometric ratios catalyst / starch (0.8; 0.7; 0.3) in order to evaluate the effectiveness of the catalyst with respect to the degree of modification, reporting that as the stoichiometric ratio catalyst / starch decreases the degree of substitution decreases (p ≤ 0.05), a similar case occurs in % fat, % protein, % humidity and % ash (p ≤ 0.05) unlike % carbohydrates and % fiber, demonstrating that the reaction conditions and the variables affect the proximate composition of the acetylated starches; and with respect to the functional properties of starches when subjected to increasing temperatures ranging from 50 ° C to 90 ° C there is a greater increase in their properties, while their apparent density and gelatinization temperature increased as the catalyst ratio decreased (p ≤ 0.05), the opposite of the % oil absorption capacity (p ≤ 0.05). For the formulation of the films, the high degree of substitution starch GS = 0.1201 ± 0.0034 was taken into account, based on a 3² experimental design; to evaluate the effect of the % of AE oregano and % B: microcrystalline cellulose on their properties; determining that it significantly affects (p <0.05) the moisture content and solubility in the films, decreasing it; Meanwhile, the mechanical properties of the films obtained from the % of AE oregano in the films decreases the tensile strength and % B: microcrystalline cellulose will require more tensile strength in the films (p<0.05)
El presente trabajo tuvo la finalidad del desarrollo de evaluar las propiedades físicas y mecánicas de films a partir de almidón acetilado de papa china Colocasia esculenta con celulosa microcristalina y aceite esencial de orégano (Origanum vulgare). Para la extracción del almidón nativo se aplicó molienda Húmeda con una solución de ácido cítrico al 0,1% (p/v) donde se obtuvo un rendimiento del 19,55 ±0,66 % , luego se realizó una modificación química por acetilación usando tres diferentes relaciones estequiométricas catalizador/almidón (0,8;0,7;0,3) con la finalidad de evaluar la efectividad del catalizador con respecto al grado de modificación, reportando que a medida que va disminuyendo la relación estequiométrica catalizador/almidón el grado de sustitución disminuye (p ≤ 0,05),caso similar ocurre en % grasa, %proteína, %humedad y %ceniza (p ≤ 0,05) a diferencia de %hidratos de carbono y %fibra , demostrando que las condiciones de la reacción y de las variables afectan la composición proximal de los almidones acetilados; y con respecto a las propiedades funcionales de los almidones al ser sometido a temperaturas crecientes que van desde los 50 °C hasta los 90 °C hay un mayor aumento en sus propiedades, en tanto a su densidad aparente y temperatura de gelatinización se incrementaron a medida que disminuye la relación del catalizador (p ≤ 0,05), lo contrario del %capacidad de absorción de aceite (p ≤ 0,05).Para la formulación de los films, se tomó en cuenta el almidón de alto grado de sustitución GS= 0,1201±0,0034, basándose en un diseño experimental 3²; para evaluar el efecto del % de AE orégano y % B:celulosa microcristalina en sus propiedades; determinándose que afecta significativamente (p<0,05) el contenido de humedad y solubilidad en los films disminuyéndolo; mientras tanto las propiedades mecánicas de los films obtenidas él % de AE orégano en las películas disminuye la fuerza de tensión y % B: celulosa microcristalina hará que se requiera de más fuerza de tensión en las películas (p<0,05).
Keywords: ACETILACIÓN; QUÍMICA; CELULOSA; FÍSICA; TENSIÓN; PELICULA